Penerapan Media Vidicard (Video and Diversity Card) Berbasis Model Problem Based Learning untuk Peningkatan Hasil Belajar Siswa Kelas VI - Mayada, Tiara Liza; Purwati, Panca Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was motivated by students' lack of activity in learning and the lack of supportive learning media. The objectives of this research are (1) to describe the application of Vidicard (video and diversity card) media based on the Problem Based Learning model and (2) to determine the increase in student learning outcomes with Vidicard (Video and Diversity Card) media based on the Problem Based Learning model. The research method used is descriptive qualitative. Research data was collected through observation, tests and literature study. The subjects in this research were 23 class VI students at SDN Ngaliyan 05. The research results show an increase in Pancasila Education learning outcomes for class VI students by using video-based learning media in the PBL model. It can be concluded that the use of video-based learning media in the PBL model can improve learning outcomes with an average value of 10.9 and a percentage increase in the completeness of student learning outcomes of 8%.